Model Tindakan Iklim Untuk Negara Berkembang (Indonesia) Melalui Metode Adaptasi Dan Mitigasi Yang Terintegrasi - Dewi Nurvianti; -, Srifridayanti; Fathurrahman (Journal Of Law And Social Society, 2024)
Climate action is the 13th Sustaianble development Goals (SDG’s) target, where countries around the world have agreed to fulfil it through concrete steps. Surely, these efforts will not be uniform among countries, including Indonesia as developing country. Well known the high costs of supporting climate actions is the biggest problem. However the challenge is even greater because Indonesia is the state with the highest gas emissions in Southeast Asia, even 3 to 4 times greater than other ASEAN member states. Therefore, it is urgent to provide recommendations for Indonesia regarding climate action models. This study used the socio-legal method. The results are: firstly, climate change has adverse effects in Indonesia, such as high levels of extreme poverty, vulnerability to food sources on which Indonesian people heavily depend, an increase in natural disasters, adverse impacts on coastal communities, and high deforestation rates. Secondly, for the effectiveness and efficiency of achieving climate action targets in Indonesia, one of the appropriate model or concept which suitable for Indonesia is a form of climate action model through synergy across aspects and sectoral, which are based on the Adaptation and Mitigation of Climate Change. This model can serve as a reference for developing countries worldwide.